Days and termal time to flowering and fructification of solanaceae crops cultivated under greenhouse in La Plata - Guaymasí, Delfina Victoria (2018)
In tomato (Solanum lycopersicum L.), pepper (Capsicum annuum L.) and eggplant (Solanum melongena L.) crops, there is a continuous introduction of hybrids, and it is of interest to study their adaptation to local growing conditions. The aim of this work was to characterize tomato, pepper and eggplant hybrids, according to thermal time and days from transplant required to reach flowering and fruiting between the first and fourth bunch. Crops were grown under a greenhouse located in La Plata, Buenos Aires, Argentina (34° 58´S, 57° 54´W). Tomato hybrids: Elpida and Griffy (Enza Zaden®), bell pepper hybrids: Almuden and Platero (Syngenta®) and eggplant hybrids: Barcelona (Fito®) and Monarca (Rijk Zwaan®) were planted on 08/14/2011. Air temperature and date of first flowering and fruiting from first to fourth bunches were registered. Days between transplant and start of phases and thermal time with a base temperature of 10 ºC for tomato and bell pepper and 11 ºC for eggplant were calculated. Statistical design was a randomized complete block with 4 replications. Number of days data were subjected to the non-parametric Friedman test and thermal time to analysis of variance (p<0.05). No statistical differences between hybrids were observed to reach first flowering or fruiting from first to fourth bunch, considering that under these trial conditions, the selection of these genetic materials for production can be done by different criteria than bioclimatic response.